2017
DOI: 10.2196/jmir.6749
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of the Italian Version of the eHealth Literacy Scale Using Item Response and Classical Test Theory Methods

Abstract: BackgroundThe eHealth Literacy Scale (eHEALS) is a tool to assess consumers’ comfort and skills in using information technologies for health. Although evidence exists of reliability and construct validity of the scale, less agreement exists on structural validity.ObjectiveThe aim of this study was to validate the Italian version of the eHealth Literacy Scale (I-eHEALS) in a community sample with a focus on its structural validity, by applying psychometric techniques that account for item difficulty.MethodsTwo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
112
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 42 publications
22
112
4
Order By: Relevance
“…The factor structure and variance of eHEALS scores may differ as a function of age, which could influence results from eHEALS studies including younger versus older samples. Diviani et al [ 34 ] conducted a validation study of the Italian version of eHEALS administered among young to middle-aged adults (mean age 37.37 years, SD 13.78). Confirmatory factor analysis results showed suboptimal model fit among 2 rival models (1-factor structure vs 2-factor structure), yet parametric and nonparametric item response theory (IRT) analyses confirmed that the single-factor model best fit the data in the study sample.…”
Section: Introductionmentioning
confidence: 99%
“…The factor structure and variance of eHEALS scores may differ as a function of age, which could influence results from eHEALS studies including younger versus older samples. Diviani et al [ 34 ] conducted a validation study of the Italian version of eHEALS administered among young to middle-aged adults (mean age 37.37 years, SD 13.78). Confirmatory factor analysis results showed suboptimal model fit among 2 rival models (1-factor structure vs 2-factor structure), yet parametric and nonparametric item response theory (IRT) analyses confirmed that the single-factor model best fit the data in the study sample.…”
Section: Introductionmentioning
confidence: 99%
“…IRT [27,46] is one of the most widely used approaches for item evaluation and test construction [29,30,47]. For example, the Patient Reported Outcomes Measurement Information System funded by the National Institutes of Health has used IRT to characterize item banks and to support computerized adaptive testing [28].…”
Section: Methodsmentioning
confidence: 99%
“…From these notes, a group of physicians and medical researchers generated questions using the Sentence Verification Technique (SVT) [24-26]. We obtained responses for these questions from the crowdsourcing platform Amazon Mechanical Turk (AMT) and analyzed the results using item response theory (IRT) [27-30] to select a subset of questions for a test of EHR note comprehension. To the best of our knowledge, the ComprehENotes question set is the first instrument to assess EHR note comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…These socio-demographic differences are consistent for mHealth use, health literacy, eHealth Literacy and Media Health Literacy, particularly with regard to education and age, and secondarily with regard to gender and ethnic background. Cultural background has also been considered to significantly influence eHealth Literacy and Media Health Literacy so much so that researchers in South Korea [27] and Italy [28], conducted several validation studies for the eHEALs model to assure that it is relevant to local culture.…”
Section: The Role Of Sociodemographicsmentioning
confidence: 99%